Groundwater Quality and Role of the Monsoon in Chennai City, South India - Sayana Vutla, Bhoga Mandala; Ravichandran, S. (Asian Journal of Chemistry, 2011)
The groundwater quality of Chennai, a metropolitan city in South India was investigated during pre and post monsoon season in 2005 to study the role of hydro geochemistry, influence of monsoon rainfall and suitability of water for domestic consumption. Seventy four water samples were collected from the urban limits of the city and analyzed for pH, electrical conductivity, alkalinity, major ions and nitrate concentration using standard methods. Sodium and chloride are the dominant cation and anion respectively. Strong alkalies dominate alkaline earth metals among cations while dominance among anions is of the order of chlorides > bicarbonates > sulphates. Seven hydro chemical facies were identified with dominant types being NaCl, NaHCO3Cl types which also showed responses to monsoon recharge. The monsoon season significantly increased the groundwater levels as well as controls the hydro chemical reactions. Contamination by sea water, especially in the eastern part of the city, onsite leaching of salts with recharge are responsible for the increased mineralization of the groundwater. The drinking water compliance for domestic uses is average for maximum allowable limits, while below average when compared with desirable limits.